Enhanced reversibility and electrochemical window of Zn-ion batteries with an acetonitrile/water-in-salt electrolyte. Issue 10 (11th January 2021) - Song, Xueyang; He, Huibing; Aboonasr Shiraz, Mohammad Hossein; Zhu, Hongzheng; Khosrozadeh, Ali; Liu, Jian
Abstract : An acetonitrile/water-in-salt (AWIS) hybrid electrolyte suppressed Zn dendrite formation, prolonged the lifetime of the Zn anode, and extended the working voltage window of Zn–MnO2 batteries from 1.8 V to 2.2 V. Abstract : An acetonitrile/water-in-salt (AWIS) hybrid electrolyte was developed for Zn-ion batteries. Compared to conventional aqueous electrolytes, the AWIS hybrid electrolyte prolonged the lifespan of Zn|Zn cells from 150 to 2500 h and increased the upper cut-off voltage from 1.8 to 2.2 V for Zn–MnO2 batteries. This new AWIS hybrid electrolyte is expected to enhance the energy and power density of Zn-based batteries for large-scale grid storage.